Sitagliptin attenuates arterial calcification by downregulating oxidative stress-induced receptor for advanced glycation end products in LDLR knockout mice - Chih-Pei Lin (Nature Portfolio, 2021)
Abstract Diabetes is a complex disease characterized by hyperglycemia, dyslipidemia, and insulin resistance. Plasma advanced glycation end products (AGEs) activated the receptor for advanced glycation end products (RAGE) and the activation of RAGE is implicated to be the pathogenesis of type 2 diabetic mellitus (T2DM) patient vascular complications. Sitagliptin, a dipeptidyl peptidase-4 (DPP4) inhibitor, is a new oral hypoglycemic agent for the treatment of T2DM. However, the beneficial effects on vascular calcification remain unclear. In this study, we used a high-fat diet (HFD)-fed low-density lipoprotein receptor deficiency (LDLR−/−) mice model to investigate the potential effects of sitagliptin on HFD-induced arterial calcification. Mice were randomly divided into 3 groups: (1) normal diet group, (2) HFD group and (3) HFD + sitagliptin group. After 24 weeks treatment, we collected the blood for chemistry parameters and DPP4 activity measurement, and harvested the aorta to evaluate calcification using immunohistochemistry and calcium content. To determine the effects of sitagliptin, tumor necrosis factor (TNF)-α combined with S100A12 was used to induce oxidative stress, activation of nicotinamide adenine dinucleotide phosphate (NADPH), up-regulation of bone markers and RAGE expression, and cell calcium deposition on human aortic smooth muscle cells (HASMCs). We found that sitagliptin effectively blunted the HFD-induced artery calcification and significantly lowered the levels of fasting serum glucose, triglyceride (TG), nitrotyrosine and TNF-α, decreased the calcium deposits, and reduced arterial calcification. In an in-vitro study, both S100A12 and TNF-α stimulated RAGE expression and cellular calcium deposits in HASMCs. The potency of S100A12 on HASMCs was amplified by the presence of TNF-α. Sitagliptin and Apocynin (APO), an NADPH oxidase inhibitor, inhibited the TNF-α + S100A12-induced NADPH oxidase and nuclear factor (NF)-κB activation, cellular oxidative stress, RAGE expression, osteo transcription factors expression and calcium deposition. In addition, treatment with sitagliptin, knockdown of RAGE or TNF-α receptor blunted the TNF-α + S100A12-induced RAGE expression. Our findings suggest that sitagliptin may suppress the initiation and progression of arterial calcification by inhibiting the activation of NADPH oxidase and NF-κB, followed by decreasing the expression of RAGE.